On some new and little-known Palaearctic species of the genus Leptochilus de Saussure, 1853 (Hymenoptera: Vespidae: Eumeninae) - Fateryga, Alexander V. (Zootaxa, 2024)
Two new species are described: Leptochilus (Euleptochilus) barkalovi Fateryga, sp. nov. from Turkmenistan and L. (Lionotulus) puzanovi Fateryga, sp. nov. from Dagestan Republic, Russia. Leptochilus barkalovi is closely related to L. (E.) limbiferus (Morawitz, 1867) from which differs, in the male sex, by narrower clypeus, blunter angles of pronotum, longer pilosity on head and mesosoma, and light-colored apical lamella of tergum 2, as well as a different structure of flagellomere 11 and aedeagus. Leptochilus puzanovi is apparently related to L. (Lionotulus) tarsatus (de Saussure, 1855) from which differs, in the female sex, by broader head, deeper emarginate apical margin of clypeus, broader mesosoma, and dark brown apical lamella of tergum 2. The hitherto unknown males of L. (Lionotulus) incertus (Kostylev, 1940) and L. (L.) leleji Fateryga, 2019 are described; the females are re-described. For the first time, L. incertus is reported from Mongolia and L. leleji from Tyva Republic, Russia. Leptochilus (Lionotulus) nacrocephalus (Kostylev, 1940), stat. nov. is raised to a full species, re-described, and reported for the first time from Armenia.